The influence of religiously motivated consumer boycotts on brand image, loyalty and product judgment - Abosag, Ibrahim (2014)
Purpose – The purpose of this paper was to examine the influence of religiously motivated boycotts, such as the one conducted in Saudi Arabia against Danish companies, on corporate brand image, customer loyalty and product judgment. Despite a growing research interest in understanding the effects of different types of consumer animosities on companies’ performance, there appears to be a scarcity of studies addressing the specific effects of religious animosity. Religious animosity is considered as an additional type which may have more stable and longer-term impacts than other animosities on behaviour. Design/methodology/approach – The study was based on a two-stage design: an exploratory qualitative stage involving 11 in-depth interviews, followed by a more comprehensive quantitative stage designed to test a proposed theoretical model. Data was collected from Saudi customers of the Danish company Arla Foods in Saudi Arabia. Data was analysed using structural equation model (LISREL 8). Findings – The model confirms that boycotting have strong negative impact on brand image and consumer loyalty but does not influence consumers’ product judgment. Practical implications – Religious boycotts have significant consequences on both corporate profits and brand image. The study provides clear steps for companies to combat the influence of religious boycotts especially in relation to brand image and customer loyalty. Originality/value – The study tested the influence of consumer religious boycotts on brand image and customer loyalty. Religious animosity was found to cause a more persistent boycott that negatively impacts brand image and weakens customer loyalty. However, by and large, boycotting was found not to have any significant impact on product judgment.